2018
DOI: 10.1111/jgs.15227
|View full text |Cite
|
Sign up to set email alerts
|

The Health of Older Americans: A Primer on Medicare and a Local Perspective

Abstract: Our work with older adults, particularly those with limited incomes, has provided significant insight into the complexities of Medicare and the U.S. healthcare system. This article provides a brief history and overview of Medicare; describes the array of insurance choices Medicare beneficiaries face; and considers the effect of income, race, and health literacy on an individual's ability to navigate Medicare. We discuss how health is more than healthcare service delivery and that it takes community efforts to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…16,17 Earlier studies reported that the rate of cost-related medication nonadherence among older adults was 5.4% in 2004 and dropped to 3.6% in 2006, likely representing the impact of the passage of the Medicare Modernization Act in 2003, which led to the full implementation of Medicare Part D in 2006. 15,18 Furthermore, while there are many studies reporting the prevalence of and factors associated with medication nonadherence, they are often outdated, [19][20][21] exclude older adults, 22,23 have limited generalizability, 21,24 or do not elicit cost-specific medication nonadherence and its reasons among older adults. 25,26 In comparison to younger individuals, older adults have an increased risk of medication nonadherence because of multiple chronic conditions and higher medication use.…”
mentioning
confidence: 99%
“…16,17 Earlier studies reported that the rate of cost-related medication nonadherence among older adults was 5.4% in 2004 and dropped to 3.6% in 2006, likely representing the impact of the passage of the Medicare Modernization Act in 2003, which led to the full implementation of Medicare Part D in 2006. 15,18 Furthermore, while there are many studies reporting the prevalence of and factors associated with medication nonadherence, they are often outdated, [19][20][21] exclude older adults, 22,23 have limited generalizability, 21,24 or do not elicit cost-specific medication nonadherence and its reasons among older adults. 25,26 In comparison to younger individuals, older adults have an increased risk of medication nonadherence because of multiple chronic conditions and higher medication use.…”
mentioning
confidence: 99%
“…The Balanced Budget Act of 1997 created Part C, giving individuals the option to enroll in Medicare managed care, and the Medicare Modernization Act of 2003 created Part D, which provides outpatient pharmacy coverage for prescription drugs. Individuals may purchase a stand‐alone Part D plan or enroll in a managed care plan (Part C) that includes prescription drug coverage …”
Section: The Many Moving Parts Of Medicarementioning
confidence: 99%
“…In general, inpatient hospitalizations (Part A) are subject to a deductible ($1,340 in 2018) for each benefit period, and the beneficiary pays nothing else out of pocket (including no premiums for most beneficiaries) unless they are hospitalized for longer than 60 days. The benefit period resets once a beneficiary has been out of the hospital or skilled nursing facility for 60 days . Part A covers all prescription drugs received during inpatient hospital stays at no additional cost to the beneficiary.…”
Section: The Many Moving Parts Of Medicarementioning
confidence: 99%
See 2 more Smart Citations